Efficient monitoring and control in intangibles-driven economies: is full independence always required? - Yuri Biondi; Pierpaolo Giannoccolo; Antoine Reberioux (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
The current crisis puts at issue the self-regulated market system of monitoring and control. Claims for restoring the proper functioning of market economies in general, and financial markets in particular, call for either establishing new sets of rules or creating new supervising authorities. Both claims rely on the received mantra of full independence that applies whenever control is concerned. However, our analysis pays attention to a neglected aspect of monitoring and control, which requires the capability to discovering and understanding flaws in and dangers from the inner congeries of the business affair under examination. Arguably, this businessspecific expertise and independence trade off. To overcome this problem, an optimal share of non-independent controllers may be chosen from or appointed by stakeholding constituencies of the business affair. They can provide proficient monitoring and control without colluding, in principle, with executive managers of the activity to be controlled.
Keywords: 330